Fra Praga e la Palestina: l’incontro di Kafka con Jakob Rabinowitz (ENTHYMEMA, 2017)
Nel luglio 1920 gli incontri con Jakob Rabinowitz, scrittore e agricoltore in Palestina, affascinarono a tal punto Kafka da toglierli il sonno. Questo contributo fa luce su un episodio sconosciuto nel quale si delineano due dimensioni opposte, e secondo Rabinowitz sostanzialmente incompatibili, della scrittura e dell’identità ebraica.In July 1920 Jakob Rabinowitz’s narratives of his life as a writer and farmer in Palestine fascinated Franz Kafka so much that it cost him «half a night thinking of them». This paper attempts to throw light on a hitherto unknown episode in Kafka’s life in which two different paths of literature and Jewish identity delineate themselves, two paths which, according to Rabinowitz, exclude each other: the abstract-calculating path of the western Jewish writers and the path bound to the sanctity of «Reality» of future Hebrew literature in Palestine.